Assembly and comparative analysis of the first complete mitochondrial genome of Citrus medica (Rutaceae) - Wu, Xiaoxue; Liu, Hong; Liao, Siyu; Liu, Xinhui; Xie, Tao; Zheng, Lixia; Hong, Yu; Chen, Wensheng; Li, Tao (Frontiers in Plant Science, 2025)
IntroductionCitrus medica, a phylogenetically pivotal progenitor of contemporary citrus cultivars, holds significant economic value due to its medicinal compounds and its role in breeding stress-resistant hybrids. The essential functions of organellar genomes in plant adaptation and metabolic regulation necessitate the characterization of their architecture to elucidate the genomic basis for these traits. However, the absence of a complete mitochondrial genome has hindered investigations into inter-organellar interactions and diversification mechanisms within this key species.MethodsTo address this gap, we used hybrid Illumina-Nanopore sequencing to produce the first mitochondrial genome of C. medica. Subsequent annotation and comparative analysis were conducted to identify homologous fragments transferred from the chloroplast genome, repetitive sequences, and RNA editing sites. Phylogenetic reconstruction was performed using 19 mitochondrial genomes, and synteny analysis was employed to assess structural divergence.ResultsThe mitochondrial genome of C. medica was assembled to a length of 553,930 bp with a GC content of 45.04%, containing 65 genes (36 protein-coding genes, 25 tRNAs, and four rRNAs). Comparative analysis revealed 44 homologous fragments (totaling 41,479 bp) transferred from the chloroplast genome, including two 6,767 bp segments containing 11 genes (rps7 and 10 tRNAs), with nine tRNA genes being either pseudogenized or lost from the chloroplast genome. The mitogenome includes 633 repetitive sequences (386 dispersed, 215 simple sequence repeats, 32 tandem), with inverted repeats exceeding 11 kb potentially facilitating recombination. Additionally, we predicted 600 RNA editing sites (predominantly C-to-U) in 34 protein-coding genes, affecting amino acid hydrophobicity in 38.83% of these sites. Phylogenetic reconstruction using 19 mitochondrial genomes positioned C. medica closest to C. unshiu. Synteny analysis highlighted significant structural divergence among Rutaceae mitochondrial genomes, with nucleotide diversity (Pi) indicating 15 polymorphic genes.DiscussionThis study establishes a foundational mitogenomic resource for C. medica, demonstrating significant acquisition of chloroplast-derived sequences and dynamic genome architecture, thus advancing the understanding of organellar evolution in citrus and supporting the breeding of stress-resistant cultivars.